Determinasi Harga Saham pada Perusahaan Sektor Transportasi dan Logistik yang Terdaftar di Bei Tahun 2021-2023 - Desta Aprilia Putri Cantika; Ismunawan Ismunawan (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to determine the influence of Return on Assets (ROA), Return on Equity (ROE), Debt to Equity Ratio (DER), Current Ratio (CR) and the exchange rate partially towards the stock prices of transportation and logistics sector companies registered in Indonesia Stock Exchange in 2021-2023. This study used quantitative research method. The population in this study was transportation and logistics sector companies registered in Indonesia Stock Exchange (IDX). The sample used was 27 companies using the total sampling method. The analysis tool used is the analysis tool multiple linear regression analysis tested using Statistical Package for the Social Science (SPSS). The results of the research conducted indicated that partially, variables namely ROA, ROE, DER and CR, do not have a significant influence towards the stock prices of transportation companies registered in the IDX in 2021-2023, while the exchange rate variable have a significant influence towards the stock prices of transportation companies registered in the IDX in 2021-2023. It is recommended that the companies can increase its value with effective steps to increase company profits.